Investigação de processos oxidativos avançados isolados e conjugados no tratamento de lixiviado bruto e antigo visando reúso - Pereira, Samara Teixeira (2018)
The treatment of leachate from landfills is considered one of the major challenges in terms of water pollution and solid waste management, especially due to its high polluting potential, with high concentration of refractory organic matter. In this context, the present work had the objective of investigating the treatment potential for crude leachate with characteristics of old, for the removal of organic matter, from combinations of advanced oxidative processes (POAs), as well as to define the reuse alternatives of leachate treated. The object of study was the crude leachate from the Metropolitan Sanitary Landfill of João Pessoa (ASMJP), created on 08/05/2003. For this, was evaluated the efficiency of the color removal and COD of the routes of treatments composed by applications of conjugated forms and isolated of the following POAs: TiO2/UV-A; H2O2/UV-C; H2O2/UVsolar; photo-Fenton solar and Fenton. POAs were tested under different time conditions and reagent concentration. The results showed that the crude leachate from ASMJP presented high color characteristics (9425.22 mg/LPt-Co) and organic matter concentration, in terms of COD (6273.32 mg of O2.L-1). The treatment route H2O2/UV-C followed by solar photo-Fenton and the treatment route H2O2/UV-C followed by Fenton, both with 60 minutes of treatment, and the solar photo-Fenton applied directly to the crude leachate with 120 minutes of treatment, reached removals above 90% for color and 70% for COD. In these conditions, the direct photo-Fenton in the raw leachate guaranteed the best quality of the treated effluent, highlighting high COD removal, lower sludge generated and lower percent residual peroxide. After the treatment of the three routes referred to above, the leachate complied with the limits imposed by the Resolution of COEMA February 02, 2017 of the state of Ceará, for the direct reuse of non-potable water for urban, agricultural, environmental and aquaculture purposes. Therefore, the results found highlight and prove the important role of the treatment and destination of leachate, which can contribute to the better development of urban solid waste management. The treatment of the leachate followed by the reuse will reflect in benefits, mainly, referring to the reduction of the pollutant load in water bodies and in the soil, demand of the consumption of drinking water and application of reuse water for less noble uses.